PEMANFAATAN KARBON AKTIF DARI LIMBAH KULIT PISANG JENIS KEPOK (MUSA ACUMINATA L.) SEBAGAI ADSORBEN DALAM MEREDUKSI EMISI GAS BUANG PADA BENTOR - Mohammad Mirwan; Rela Desi Puji Lestari (EnviroUS, 2022)
Bentor is a combination of rickshaw and motor, the smoke emitted by bentor has a high air pollutant content. One of them is Carbon Monoxide (CO). CO pollutants are dangerous compounds contained in exhaust smoke, if the smoke is scattered more and more in the air it will pollute the air and human health. CO pollutants can be minimized by adsorption. Adsorption is the process of absorbing a hazardous compound. This research utilizes kepok banana peel which is processed into activated carbon which will be used as an adsorbent to adsorb CO. Musa Acuminta Linn was carbonized and then activated using H2SO4 solution. This research modifies the bentor exhaust mixing addition of an adsorbent weighing 50 grams and is included in the exhaust. Behind the results of the research on the characteristics of activated carbon on the iodine absorber of 31%, it proves that the activated carbon from the kepok banana peel has met the requirements for activated carbon in accordance with the Indonesian Industrial Standard No. 0258.88 and this has an effect on decreasing the concentration of CO, which is able to reduce CO levels by 2% at idle conditions in the test time of 15 minutes.